Artificial Intelligence: Implication on Management - Ballamudi, Koteswara Rao (i-Proclaim, 2019)
The advancement in Artificial Intelligence (AI) is surging and it is at the center of improved output. Consequent to the advancement in the science of AI, human-to-machine interactions are facilitated, business models and logic now vary, and the lifestyle, as well as the living standards of humans, has changed. Artificial Intelligence (AI) is often regarded as a complex unit. There are many descriptions and numerous more impressions of what makes up Artificial Intelligence. The risk implications of Artificial Intelligence vary and it’s dependent on the degree of its usage. The advantages of artificial intelligence outnumber the risks it conveys, particularly in the world of business usage and its application is resulting in a world that is innovative and smarter. With the expectation that professions will be impacted, it conveys immediate effect on firms, their workers, and organizational management. The current study sought to answer some research questions; Is there knowledge about the effects of Artificial Intelligence on management? What is the current prediction for the future of management as it relates to the emergence of Artificial Intelligence? Does the current study specify the duties of middle managers in the future following the rise in AI? It adopted the systematic literature review approach where relevant literature is selected and used for the analysis.  Following Jesson, Matheson & Lacey (2011) approach to systematic review to include; (a) Mapping the area through a scoping review, b) Detailed domain search, c) Quality appraisal, d) Data gathering e) Synthesis, and f) Report writing, over 100 papers on the subject were selected. On screening, it was reduced to about 15 papers with a direct relationship on the subject. The study found out that; AI is a necessary evil to and for the future of firms.  It will have varying degrees of effect on management. AI technology will discharge managerial assignments and will be helpful in addressing management challenges. Managers and management, therefore, need to get new competencies and skills to tap into new frontiers that are AI-based.